Decision quality and satisfaction: the effects of online information sources and self-efficacy. Issue 4 (7th August 2017) - Yan, Yalan; Zhang, Xi; Zha, Xianjin; Jiang, Tingting; Qin, Ling; Li, Zhiyuan
Abstract : Purpose: Digital libraries and social media are two sources of online information with different characteristics. The purpose of this paper is to integrate self-efficacy into the analysis of the relationship between information sources and decision making, and to explore the effect of self-efficacy on decision making, as well as the interacting effect of self-efficacy and information sources on decision making. Design/methodology/approach: Survey data were collected and the partial least squares structural equation modeling was employed to verify the research model. Findings: The effect of digital library usage for acquiring information on perceived decision quality (PDQ) is larger than that of social media usage for acquiring information on PDQ. Self-efficacy in acquiring information (SEAI) stands out as the key determinant for PDQ. The effect of social media usage for acquiring information on PDQ is positively moderated by SEAI. Practical implications: Decision making is a fundamental activity for individuals, but human decision making is often subject to biases. The findings of this study provide useful insights into decision quality improvement, highlighting the importance of SEAI in the face of information overload. Originality/value: This study integrates self-efficacy into the analysis of the relationship between information sources and decision making, presenting a new perspective for decision-making research and practice alike.